Ni Krining, Antara Pengorbanan dan Perlawanan dalam Budaya Patriarki Bali - Khothibul Umam (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
A literature is a reflection of real world reality. A writer wrote it in a literary work. One of the themes of short stories in Indonesia is the theme of women's resistance in traditional and cultural circles. The short story